(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
This Research Deals With An Important Issue In The Fundamentals Of Maliki Jurisprudence, Which Is An Issue That Legal Rulings Are Affected By The Current Customs And Habits In Various Societies And Environments. This Research Has Tried To Answer Several Questions, The Most Prominent Of Which Are: What Is Custom And Habit? Are There Conditions That Take Into Account The Custom? What Are The Custom’s Functions And Fields? What Is The Relationship Between Custom And Some Deductive Principles In The Maliki School Of Thought? What Is The Effect Of Custom On The Legal Provisions? This Research Combined Theoretical Rooting And Application, As It Mentioned Some Jurisprudential Applications From The Maliki School Of Thought, Which Seeks To Study The Impact Of Custom And Custom On It. Key Words- Observance ,Custom , Custom , Doctrine , Maliki